2005
DOI: 10.3201/eid1102.040691
|View full text |Cite
|
Sign up to set email alerts
|

Survey for Bat Lyssaviruses, Thailand

Abstract: Surveillance for lyssaviruses was conducted among bat populations in 8 provinces in Thailand. In 2002 and 2003, a total of 932 bats of 11 species were captured and released after serum collection. Lyssavirus infection was determined by conducting virus neutralization assays on bat serum samples. Of collected samples, 538 were either hemolysed or insufficient in volume, which left 394 suitable for analysis. These samples included the following: Pteropus lylei (n = 335), Eonycteris spelaea (n = 45), Hipposideros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 53 publications
(28 citation statements)
references
References 9 publications
3
25
0
Order By: Relevance
“…Nevertheless, we are also aware that there may be other vectors, such as bats, and other lyssaviruses, besides genotype 1, circulating in Thailand. In fact, our recent survey in Thai bats indicated that as many as 7.5% of the bat population had evidence of lyssavirus infection by an as yet unidentified genotype(s) [13]. …”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, we are also aware that there may be other vectors, such as bats, and other lyssaviruses, besides genotype 1, circulating in Thailand. In fact, our recent survey in Thai bats indicated that as many as 7.5% of the bat population had evidence of lyssavirus infection by an as yet unidentified genotype(s) [13]. …”
Section: Discussionmentioning
confidence: 99%
“…In addition, a very closely related species, Rousettus leschenaulti is distributed broadly in southern Asia, and data on bat lyssaviruses from that area are very limited (35,36,48,55). Most of the roosts of E. helvum and R. aegyptiacus encountered in Kenya were situated within or in close proximity to human settlements.…”
Section: Discussionmentioning
confidence: 99%
“…Old World fruit bats are natural reservoirs to a number of such diseases, including several emerging viruses that have limited or no pathogenicity in their bat hosts but high fatality rates in people. These include Ebola viruses (Leroy et al 2005), Marburg virus (Towner et al 2009), Nipah virus (Rahman et al 2013), Hendra virus (Halpin et al 2000), and lyssaviruses in Australia (Mackenzie et al 2003) and Thailand (Lumlertdacha et al 2005). While the transmission pathway for each virus is not always known, there is compelling evidence, in a small number of cases, that points to a food-borne route, most notably multiple spillover events of Nipah virus from Pteropus giganteus to people in Bangladesh (see below).…”
Section: Food-borne Zoonotic Disease Risk From Pteropodid Batsmentioning
confidence: 99%